2021
DOI: 10.3389/fpsyg.2021.663317
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Knowledge Base and Innovation-Driven Growth: Moderated by Organizational Character

Abstract: Purpose: On the background of innovation-driven growth strategy of the Chinese government, this study aims to explore the impact of the knowledge base on innovation-driven growth of a firm, which is moderated by organizational character.Design/methodology/approach: Based on the data of 965 Chinese listed companies, some hypotheses were tested using the method of hierarchical regression analysis.Findings: Organizational growth relies on both technological and business model innovations and their interactive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…This study promotes the integration and development of some theories such as knowledge base, exploratory innovation, exploitative innovation, and data mining. Knowledge base are regarded as an important source of firms' sustainable competitive advantage (Yu and Yan, 2021 ; Low and Ho, 2016 ). Based on the knowledge-based view and data mining and other related theories, this study constructs the theoretical model of the relationship between the knowledge base and dual-innovation performance of firms and analyzes the influence of knowledge-base features on the dual-innovation performance of firms in different clusters.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study promotes the integration and development of some theories such as knowledge base, exploratory innovation, exploitative innovation, and data mining. Knowledge base are regarded as an important source of firms' sustainable competitive advantage (Yu and Yan, 2021 ; Low and Ho, 2016 ). Based on the knowledge-based view and data mining and other related theories, this study constructs the theoretical model of the relationship between the knowledge base and dual-innovation performance of firms and analyzes the influence of knowledge-base features on the dual-innovation performance of firms in different clusters.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Meanwhile, it is also difficult to be cracked, imitated, and chased by other competitors. Therefore, the knowledge base is not only a decisive resource for firms but also an important component of their sustainable competitive advantage (Yu and Yan, 2021 ; Low and Ho, 2016 ). A firm with a stronger knowledge base can predict the future more accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Learning from the previous study (Yu and Yan, 2021 ), we designed four control variables as the alternative explanations for firm growth. First, we set ownership as a dummy variable that controls for potential variations between state-owned enterprises (coded as 1) and private-owned, foreign-owned, or other types of enterprises (coded as 0).…”
Section: Methodsmentioning
confidence: 99%
“…From a macro perspective, Dalgıç and Fazlıoğlu ( 2021 ) emphasized that firm growth capability can be assessed from employment growth and sales growth. From a micro perspective, Yu and Yan ( 2021 ) argued that firm growth capability should be evaluated by income growth and assets growth. However, these studies generally measured “how much” a firm grows, but ignored investigating “how” the firm grows (McKelvie and Wiklund, 2010 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the field of external collaboration, its breadth and depth have been repeatedly employed to address research questions [ 25 , 26 ]. Extant studies have shown that both are beneficial to enterprise innovation [ 19 , 27 ]. Thus, we proposed that the two are also important antecedents of business model innovation.…”
Section: Introductionmentioning
confidence: 99%